(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Periodontitis is an acute or chronic dental disease accompanied by an inflammatory process in the tissues that support the tooth in its normal position. The disease is characterized by inflammation of the periodontal tissues of varying severity. Sometimes the pathological process does not manifest itself at all for a long time. There are no clinical manifestations. At the same time, destruction still occurs, it does not go away on its own and does not disappear anywhere. Only a dentist or periodontist can diagnose periodontitis by conducting a series of appropriate studies. Pathology is treated in a comprehensive manner. Correction of the inflammatory process and professional hygiene are carried out. With a competent, qualified approach, there are all chances to cope with the disease and achieve a complete cure.